The Effect of Garlic and Voluntary Exercise on Cardiac Angiogenesis in Diabetes: The Role of MiR-126 and MiR-210 - Naderi,Roya (2019)
Abstract Background: Diabetes mellitus (DM) is one of the major risk factors for cardiovascular disease, leading to endothelial dysfunction and angiogenesis impairment . MiR-126 and miR-210 support angiogenic response in endothelial cells. Objective: The present study sought to explore the effect of garlic and voluntary exercise, alone or together, on miR-126 and miR-210 expressions and cardiac angiogenesis in rats with type 1 diabetes. Methods: Male Wistar rats were divided into five groups (n = 7): Control, Diabetes, Diabetes+Garlic, Diabetes+Exercise, and Diabetes+Garlic+Exercise. Diabetes was induced in the animals by streptozotocin (ip, 50 mg/kg). The rats were then fed raw fresh garlic homogenate (250 mg/kg) or were subjected to voluntary exercise, or to combined garlic and voluntary exercise for 6 weeks. MiR-126 and miR-210 expressions in the myocardium were determined by real time PCR, and the serum lipid profile was measured by enzymatic kits. Angiogenesis was evaluated by immunostaining for PECAM-1/ CD31 in the myocardium. Results: Diabetes reduced both cardiac miR-126 expression and angiogenesis (p < 0.05). On the other hand, there was a miR-210 expression increase in the myocardium of diabetic animals (p < 0.001). However, those effects reversed either with garlic or voluntary exercise (p < 0.01). Moreover, treating diabetic rats with garlic and voluntary exercise combined had an additional effect on the expressions of miR-126 and miR-210 (p < 0.001). Furthermore, both voluntary exercise and garlic significantly improved serum lipid profiles (p < 0.001). Conclusion: The induction of diabetes decreased angiogenesis in the myocardium, whereas our treatment using long-term voluntary exercise and garlic improved myocardial angiogenesis. These changes were possibly owing to the enhancement of myocardial miR-126 and miR-210 expressions.